Association between choline supplementation and Alzheimer’s disease risk: a systematic review protocol - Aguree, Sixtus; Zolnoori, Maryam; Atwood, Thea Patricia; Owora, Arthur (Frontiers in Aging Neuroscience, 2023)
Background and Aims: There is growing evidence suggesting choline intake might have beneficial effects on cognitive function in the elderly. However, other studies reported no relationship between choline intake and cognitive function or improvement in Alzheimer's disease patients. This protocol is for a systematic review of choline intake and Alzheimer's disease that aims to assess the comparative clinical effectiveness of choline supplementation on Alzheimer's disease risk. Methods and analysis: literature search will be performed in PubMed, MEDLINE, EMBASE, CINAHL, Scopus, Cochrane, and the Web of Science electronic databases from inception until July 2023. We will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies will be included if they compared two different time points of choline biomarkers measures in men or women (65+) with Alzheimer's Disease. The risk of bias in the included studies will be assessed within the Covidence data-management software. Results: This review will summarize the clinical trial and quasi-experimental evidence of choline intake on Alzheimer's disease risk for adults aged 65+. The results from all eligible studies included in the analysis will be presented in tables, text, and figures. A descriptive synthesis will present the characteristics of included studies (e.g., age, sex of participants, type, length of intervention and comparator, and outcome measures), critical appraisal results, and descriptions of the main findings. Discussion: This systematic review will summarize the existing evidence on the association between Choline intake and AD and to make recommendations if appropriate. The results of this review will be considered with respect to whether there is enough evidence of benefit to merit a more definitive randomized controlled trial. The results will be disseminated through peer-reviewed journals population.This protocol outlines the methodology for a systematic review of choline intake and AD. The resulting systematic review from this protocol will form an evidence-based foundation to advance nutrition care for individuals with AD or poor cognitive function. Systematic review registration: www.crd.york.ac.uk/PROSPERO, identifier: CRD42023395004.